Perlindungan Hukum Investor terhadap Penggelapan Dana oleh Perusahaan Sekuritas di Pasar Modal Indonesia (Studi Kasus PT Yulie Sekuritas Indonesia) - Zfika Amanda Fitria Azil Rahmawati Fauziah (Program Studi Ilmu Hukum, Universitas Kuningan, 2026)
Legal protection for investors is a fundamental principle in the operation of the Indonesian capital market, particularly in preventing and addressing embezzlement or misuse of investor funds by securities companies. Despite comprehensive regulations in Law Number 8 of 1995 concerning Capital Markets and various regulations of the Financial Services Authority (OJK), violations in the form of embezzlement still occur. One case illustrating this problem is the case of PT Yulie Sekuritas Indonesia, which resulted in significant losses for investors due to the misuse of client funds. This article aims to analyze the legal protection provisions for investors in the Indonesian capital market and examine the application of the disgorgement fund mechanism as an embodiment of the principle of corrective justice in recovering investor losses. The research method used is normative legal research with a statutory regulatory approach and a case study approach. Data were obtained through a literature review of relevant primary, secondary, and tertiary legal materials, as well as an analysis of the PT Yulie Sekuritas Indonesia case. The results indicate that, normatively, legal protection for investors is regulated through preventive and repressive mechanisms. However, the effectiveness of this protection still faces obstacles in its implementation, primarily due to weak oversight and law enforcement. The case of PT Yulie Sekuritas Indonesia demonstrates that sanctions imposed do not fully guarantee the recovery of investor losses. Therefore, the disgorgement fund mechanism is an important instrument to strengthen legal protection for investors by returning funds resulting from violations to injured parties.